Relationship between psychological well-being and professional self-efficacy of senior pupils and students in war conditions - Muzyka, Olena (Educological discourse, 2024)
The article, based on the analysis of scientific publications, states that psychological well-being and professional self-efficacy are personal and value formations, as they integrate accumulated experience, actual ways of self-realization, goals, and directions of self-development in the future. It was also established that psychological well-being and self-efficacy have pronounced connections, which allows them to be considered as mutually determined and mutually reinforcing phenomena. The data of the empirical study show that in the conditions of military operations, high school students and students demonstrate rather low indicators of psychological well-being and professional self-efficacy, the connections between which are rather weak. Correlational and factor analyzes have identified a number of constructs on the basis of which it is possible to begin the formation of that can be used to initiate a relationship and mutual reinforcement of psychological between well-being and professional self-efficacy. These are indicators of psychological well-being such as «personal growth» and «purpose in life» as well as professional self-efficacy – including «resistance to failure, overcoming adversity and will». Since in the conditions of war it is hardly possible to directly influence the improvement of psychological well-being, professional self-efficacy training can be considered as a method of indirectly promoting the psychological well-being of students. It should include exercises aimed at personal and professional development, in particular at reflecting on life goals and specifying plans for their implementation in the near (current plans), medium and long term. As a result, the educational space of the university should become an environment in which each educational and professional achievement of students will contribute to the growth of their psychological well-being, and the latter will encourage them to new achievements in personal and professional development.